1998
DOI: 10.1128/aem.64.4.1510-1513.1998
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Barophilic Bacteria Isolated from the Mariana Trench, Challenger Deep, at a Depth of 11,000 Meters

Abstract: Two strains of obligately barophilic bacteria were isolated from a sample of the world’s deepest sediment, which was obtained by the unmanned deep-sea submersible Kaiko in the Mariana Trench, Challenger Deep, at a depth of 10,898 m. From the results of phylogenetic analysis based on 16S rRNA gene sequences, DNA-DNA relatedness study, and analysis of fatty acid composition, the first strain (DB21MT-2) appears to be most highly similar to Shewanella benthica and close relatives, and the second strain (DB21MT-5) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 287 publications
(117 citation statements)
references
References 19 publications
4
112
0
1
Order By: Relevance
“…The cultures incubated under high pressure (Table 3A) showed decreasing amounts of tridecanoic acid (13:0), pentadecanoic acid (15:0), and eicosapentaenoic acid (EPA, 20:5) during the culture period as observed in the case of strains belonging to the Shewanella barophiles branch, and S. benthica, and increasing amounts of tetradecenoic acid (14:1) and docosahexaenoic acid (DHA, 22:6) as observed in the case of barophilic Moritella sp. [8] (also shown in Fig. 4).…”
Section: Fatty Acid Analysissupporting
confidence: 54%
“…The cultures incubated under high pressure (Table 3A) showed decreasing amounts of tridecanoic acid (13:0), pentadecanoic acid (15:0), and eicosapentaenoic acid (EPA, 20:5) during the culture period as observed in the case of strains belonging to the Shewanella barophiles branch, and S. benthica, and increasing amounts of tetradecenoic acid (14:1) and docosahexaenoic acid (DHA, 22:6) as observed in the case of barophilic Moritella sp. [8] (also shown in Fig. 4).…”
Section: Fatty Acid Analysissupporting
confidence: 54%
“…Interestingly, most enzymes originating from deep-sea organisms remain active at high pressure, while related enzymes from land organisms lose their activity (Kato et al, 2008). For example, 3-isopropylmalate dehydrogenase (IPMDH) from the obligate piezophile Shewanella benthica DB21MT-2, originally isolated from the Mariana Trench (Kato et al, 1998;Nogi & Kato, 1999), was shown to be more tolerant to highpressure stress than the same enzyme originating from the nonpiezophile S. oneidensis MR-1 (Kasahara et al, 2009). IPMDH catalyzes the reduction of 3-isopropylmalate (IPM) to 2-isopropyl-3-oxosuccinate in the presence of divalent metal cations such as magnesium or manganese ion and nicotinamide adenine dinucleotide.…”
Section: Introductionmentioning
confidence: 99%
“…Marine environments, including the subsurface, have previously been estimated to contain a total of approximately 3AE67 · 10 30 micro-organisms (Whitman et al 1998), and given that approximately 71% of the earth's surface of 361 million square kilometers is covered by oceans, which has been estimated to account for more than 80% of life on earth; then it is clear that the marine environment, just like the more well-studied terrestrial environment, contains an enormous pool of as yet largely underexploited microbial biodiversity. This biodiversity arises primarily due to the wide variety of microbial ecosystems which are inhabited by bacteria, ranging from ocean trenches with depths of up to 11 000 m and pressures exceeding 100 MPa (Kato et al 1998) to deep-sea hydrothermal vents with temperature as high as approximately 400°C (Zierenberg et al 2000). Micro-organisms have adapted to living in these challenging environments, either surviving as free-living organisms or in association with other organisms such as marine animals.…”
Section: Introductionmentioning
confidence: 99%